2021
DOI: 10.3390/foods10081907
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Markers in Olives (Olea europaea L.): Utility in the Cataloging of Germplasm, Food Authenticity and Traceability Studies

Abstract: The olive fruit, a symbol of Mediterranean diets, is a rich source of antioxidants and oleic acid (55–83%). Olive genetic resources, including cultivated olives (cultivars), wild olives as well as related subspecies, are distributed widely across the Mediterranean region and other countries. Certain cultivars have a high commercial demand and economical value due to the differentiating organoleptic characteristics. This might result in economically motivated fraudulent practices and adulteration. Hence, tools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 132 publications
2
7
0
Order By: Relevance
“…Considering the quantities and the different phenol fractions found, it can be stated that some Maltese genotypes have important radical scavenging, antioxidant and anti-inflammatory properties [ 42 , 43 , 44 , 45 , 46 ]. The main phenolic compounds in the samples under investigation were secoiridoids and their derivatives, as has already been found in other studies [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The contribution of phenolic alcohols, such as hydroxytyrosol and tyrosol, of flavonoids with rutin and luteolin 7-glycoside and of acid phenols (particularly vanillic acid) was relevant.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Considering the quantities and the different phenol fractions found, it can be stated that some Maltese genotypes have important radical scavenging, antioxidant and anti-inflammatory properties [ 42 , 43 , 44 , 45 , 46 ]. The main phenolic compounds in the samples under investigation were secoiridoids and their derivatives, as has already been found in other studies [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The contribution of phenolic alcohols, such as hydroxytyrosol and tyrosol, of flavonoids with rutin and luteolin 7-glycoside and of acid phenols (particularly vanillic acid) was relevant.…”
Section: Discussionsupporting
confidence: 77%
“…Olive cultivars may be distinguishable based on their morphological characteristics [ 16 , 17 ], but some traits are strongly influenced by the agro-environmental conditions [ 18 ]. A big step forward for the identification of olive cultivars has been made by the application of molecular markers [ 19 , 20 , 21 , 22 ]. Mazzitelli and colleagues [ 9 ], by applying molecular analysis to the local olives of the islands, highlighted a clear separation between the two main cultivars: Bidni and Malti, with the latter being related to the San Anton variety, a giant tree considered a wild-type oleaster.…”
Section: Introductionmentioning
confidence: 99%
“…Scientific studies on olives have revealed that these products have crucial functions in human health owing to their high levels of biologically active compounds. The diversity of olive cultivars offers great opportunities for researchers to find the best species for both human nutrition and the pharmaceutical industry, as well as for future crossbreeding processes [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Several research works have been carried out to determine their distribution and characterization from the genetical, morphological, and phytochemical points of view in order to expand knowledge about traditional olive cultivars, which is undoubtedly the first step toward their protection. The biochemical analysis is crucial because it can provide information on unique biomarkers for distinct cultivars while also providing a direct indication of nutraceutical value [15,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…This was demonstrated in the case of olive species. Microsatellite markers have been employed in cultivar identification, characterization of autochthonous olives (ancient olive trees and oleasters), management of olive germplasm banks, phylogenetics, diversity analysis, and mapping, as reviewed by Yadav et al [ 10 ].…”
mentioning
confidence: 99%